TYT Curve : Pilot Study on Alternatives Standards of Reference to Determine Intrauterine Growth in Low Resource Setting In Indonesia - Tina Dewi Judistiani; Tetty Yuniaty; Yessika Adelwin Natalia (International Journal of Integrated Health Sciences, 2014)
Objective: To develop a new intrauterine growth curve based on local population for accurate intrauterine growth retardation (IUGR) infant identification. Methods: An observational analytic method was applied to develop Tina-Yessika-Tetty (TYT) curve derived from 13,405 neonatal anthropometric measurements taken from the medical record database of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. The infants included in this study were born during the period of January 1st, 2005 to December 31st, 2009. The new curve was then compared to the Lubchenco and Alisjahbana curves. Only 6,814 data met the inclusion and exclusion criteria.    Results: The mean birth weight in this study was lower compared to that of the Lubchenco and Alisjahbana studies. Comparison of the three curves showed that there was a significant difference among the three curves (R=0.998, R2=0.996, p<0.001), which indicates a probability for a newborn classification.Conclusions: TYT curve may be used as an alternative to identify IUGR immediately after birth, especially when detection during pregnancy is not available in low resource setting. A prospective study with a larger population is needed; However, this study has provided an evidence to support the need for timely evaluation for such growth chart as they change over time.    Keywords: Alisjahbana curve, intrauterine growth, Lubchenco curve, TYT curveDOI: 10.15850/ijihs.v2n1.271